Pattern of WhatsApp and Facebook usage and its impact on sleep quality among nursing students in Pondicherry - Chandramoorthy, Karthikraja; Rajendran, Prahankumar; Newtonraj, Ariarathinam; Rajamanickam, Rajalakshmi; Purty, Anil J. (International Journal Of Community Medicine And Public Health, 2021)
Background: Usage of social networking sites like WhatsApp and Facebook in smartphones has become a basic necessity in today’s life, especially among college students. However, the excess usage of mobile phone affects sleep quality and attention span. Nursing students are prone to sleep disturbance due to their academics and work pattern. The aim of the study was to assess the pattern of WhatsApp and Facebook usage among nursing students and its impact on their sleep quality. Methods: A cross-sectional study was conducted among 168 nursing students of a nursing college in Puducherry. Participants were explained about the purpose of study and written informed consent was obtained. Data was collected using a self-administered questionnaire. Sleep quality was assessed using PSQI scale. Institutional ethics committee approval was obtained for the study. The data was entered in Microsoft Excel and analyzed using STATA 14. Results: Among the study participants, most of them prefer WhatsApp over Facebook. Almost 40% of the students had poor quality of sleep. There was statistically significant association between usage of WhatsApp while feeling sleepy, while having food and poor quality of sleep. However, the adjusted prevalence ratio of poor sleep quality did not show statistical significance. Conclusions: The current study showed statistical significance between certain pattern of WhatsApp usage leading to poor sleep quality among nursing students. Thus, corrective measures have to be implemented to moderate the mobile phone usage and improve the sleep quality of nursing students.